2006
DOI: 10.15666/aeer/0402_047053
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Net Photosynthetic Rate of Temperate Dry Grassland Species and Winter Wheat at Elevated Air Co2 Concentration

Abstract: Abstract. A number of C 3 temperate dry grassland species and winter wheat plants were grown in open top chambers either at 365 µmol mol -1 (AC) or at 700 µmol mol -1 (EC) air CO 2 concentrations. Gas exchange measurements were made at several air CO 2 concentrations. When measured at higher CO 2 concentrations, net photosynthetic rate was higher in plants grown at EC than at AC. The widely accepted Farquhar net photosynthesis model was parameterized and tested using several observed data. After parameterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Photosynthetic activity of Katy was significantly increased in greenhouse, particularly when the CO 2 concentration was above 400 μmol mol -1 . The results corroborate the conclusions of earlier investigations (Szente et al 1998, Harnos et al 2002. The two cultivars differed greatly in response to irradiance (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Photosynthetic activity of Katy was significantly increased in greenhouse, particularly when the CO 2 concentration was above 400 μmol mol -1 . The results corroborate the conclusions of earlier investigations (Szente et al 1998, Harnos et al 2002. The two cultivars differed greatly in response to irradiance (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Earlier results suggested that the Farquhar model was suitable for the description of the net photosynthesis of winter wheat under various environmental conditions (radiation, temperature, atmospheric CO 2 concentration) and could thus be usefully incorporated into wheat growth simulation models [7]. In the course of the present work the Farquhar model was thus incorporated into the module of the AFRCWHEAT2 model that describes net CO 2 assimilation, thus developing the AF2MOD model.…”
Section: Discussionmentioning
confidence: 91%
“…The accuracy of biomass predictions demonstrated that the model could complement field studies and serve as a valuable tool in evaluating management of these grasses and their impact on forage productivity of a site, soil erosion, water use, nutrient cycling, and wildlife habitat. Future applications of more detailed CO 2 photosynthetic simulation models [37][38][39][40] in this context will be interesting, in light of the differences between simulated and measured values in this study.…”
Section: Discussionmentioning
confidence: 97%